The value of open access and a patient centric approach to oral oncolytic utilization in the treatment of Chronic Myelogenous Leukemia: A U.S. perspective. (4th March 2017) - Das, Lopamudra; Gitlin, Matthew; Siegartel, Lisa R.; Makenbaeva, Dinara
ABSTRACT: Introduction : Since the introduction of tyrosine kinase inhibitors (TKIs), the treatment of patients with chronic myelogenous leukemia (CML) has resulted in significant improvement in patient survival but at a higher pharmaceutical cost to payers. The recent introduction of generic imatinib presents an opportunity to lower pharmacy costs within a population that is growing due to improved survival. Recent literature has focused on the likely benefits to payers of step therapy through generic imatinib. Areas covered : This review provides a perspective that is broader than the evaluation of financial savings or narrowly defined health economic metrics by incorporating factors such as CML patient heterogeneity, including varying levels of disease progression risk, comorbidities and genetic mutation status, differences in TKI product profiles, clinical guideline recommendations, and the importance of individualized patient care. A focused literature review evaluating the real-world impact of utilization management programs is presented. Expert commentary : The findings indicate that payers can achieve substantial savings without the need to implement utilization management policies. Compromises in the ability to provide individualized patient care and unwanted economic consequences resulting from increased costs of disease progression, adverse events, and lack of response to treatment due to utilization management are summarized.